Pemberdayaan Kewirausahaan Pada Era Digital Di Kalangan Mahasiswa Universitas Negeri Padang - Michael Brian Bhayu Nainggolan; Retna Pebrianti; Nanda Aulia Pratama; Yulia Hanoselina (CV. ITTC INDONESIA, 2025)
In the digital era, entrepreneurship among university students has become increasingly relevant due to the accessibility of technology. This study aims to enhance students’ understanding of digital entrepreneurship through a structured socialization program. The approach used was participatory and informative, consisting of presentations, discussions, and Q&A sessions. The program focused on utilizing platforms such as Shutterstock, Canva, and affiliate marketing to initiate low-capital digital businesses. Conducted at Universitas Negeri Padang, the activity involved students from various departments. Data were collected using a pre-event survey and post-event questionnaire to evaluate knowledge acquisition and student perceptions. The results show increased interest and awareness among students regarding digital business opportunities. Participants reported motivation to start their own ventures using accessible digital tools. This study concludes that socialization programs are effective in fostering entrepreneurial spirit among youth, especially when practical and technology-based approaches are employed.